CCR5 Promoter Polymorphisms Associated With Pulmonary Tuberculosis in a Chinese Han Population - Liu, Shuyuan; Liu, Nannan; Wang, Hui; Zhang, Xinwen; Yao, Yufeng; Zhang, Shuqiong; Shi, Li (Frontiers in Immunology, 2021)
Background: Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, is a major public health concern. Chemokines and their receptors, such as RANTES, CXCR3, and CCR5, have been reported to play important roles in cell activation and migration in immune responses against TB infection. Methods: To understand the correlations involving CCR5 gene variations, M. tuberculosis infection, and TB disease progression, a case-control study comprising 450 patients with TB and 306 healthy controls from a Chinese Han population was conducted, along with the detection of polymorphisms in the CCR5 promoter using a sequencing method. Results: After adjustment for age and gender, the results of logistic analysis indicated that the frequency of rs2734648-G was significantly higher in the TB patient group (P = 0.002, OR = 1.38, 95% CI: 1.123-1.696); meanwhile, rs2734648-GG showed notable susceptibility to TB (P = 6.32E-06, OR = 2.173, 95% CI: 1.546-3.056 in a recessive model). The genotypic frequency of rs1799987 also varied between the TB and control groups (P = 0.008). In stratified analysis, rs2734648-GG significantly increased susceptibility to pulmonary TB in a recessive model (P < 0.0001, OR = 2.382, 95% CI: 1.663-3.413), and the rs2734648-G allele significantly increased susceptibility to TB recurrence in a dominant model (P = 0.0032, OR = 1.936, 95% CI: 1.221-3.068), whereas rs1799987-AA was associated with susceptibility to pulmonary TB (P = 0.0078, OR = 1.678, 95% CI: 1.141-2.495 in a recessive model) but not with extra-pulmonary TB and TB recurrence. A haplotype constructed with the major alleles of the eight SNPs in the CCR5 promoter (rs2227010-rs2856758-rs2734648-rs1799987-rs1799988-rs41469351-rs1800023-rs1800024: A-A-G-G-T-C-G-C) exhibited extraordinarily increased risk of susceptibility to TB and pulmonary TB (P = 6.33E-11, OR = 24.887, 95% CI: 6.081-101.841). Conclusion: In conclusion, CCR5 promoter polymorphisms were found to be associated with pulmonary TB and TB progression in Chinese Han people.